2020
DOI: 10.1080/13854046.2020.1824280
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective sleep measures are associated with neurocognition in aging adults with and without HIV

Abstract: Objective: Poor sleep quality is related to worse neurocognition in older adults and in people with HIV (PWH); however, many previous studies have relied only on self-report sleep questionnaires, which are inconsistently correlated with objective sleep measures. We examined relationships between objective and subjective sleep quality and neurocognition in persons with and without HIV, aged 50 and older. Method: Eighty-five adults (PWH n ¼ 52, HIV-negative n ¼ 32) completed comprehensive neuropsychological test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Because 30% to 50% of PLWH experience HAND, the incidence and severity of HAND may increase in the coming years and diminish quality of life (QoL; Small & Brew, 2018). In fact, PLWH with HAND have reported QoL issues associated with cognitive complaints, depression/mood problems (Waldrop et al, 2021), poor sleep quality (Campbell et al, 2020), and health-related QoL (Jones et al, 2019). Fortunately, cognitive remediation techniques, such as transcranial direct current stimulation or cognitive training to improve cognition, may improve QoL.…”
mentioning
confidence: 99%
“…Because 30% to 50% of PLWH experience HAND, the incidence and severity of HAND may increase in the coming years and diminish quality of life (QoL; Small & Brew, 2018). In fact, PLWH with HAND have reported QoL issues associated with cognitive complaints, depression/mood problems (Waldrop et al, 2021), poor sleep quality (Campbell et al, 2020), and health-related QoL (Jones et al, 2019). Fortunately, cognitive remediation techniques, such as transcranial direct current stimulation or cognitive training to improve cognition, may improve QoL.…”
mentioning
confidence: 99%
“…Better sleep latency and sleep efficiency were associated with better task completion in controls but not in PWH. Another US study ( n = 52 PWH and n = 32 controls), collected cognitive testing and 5–15 days of actigraphy data [26]. Better cognition was associated with less sleep fragmentation and greater sleep efficiency and sleep time overall but results were generally nonsignificant in the PWH stratum, with only sleep fragmentation associating with learning and recall cognitive domains and several other results just outside statistical significance thresholds.…”
Section: Cognitionmentioning
confidence: 99%
“…Self-reported sleep symptoms often lack good correlation to actigraphy-based measures [26,27], but symptoms and actigraphy capture different dimensions of sleep. Although POPPY found no association between RU-SATED sleep dimensions and cognitive test results [19 ▪▪ ], other studies have demonstrated worse cognitive test results in PWH with self-reported daytime sleepiness (reported by 67% of n = 562 PWH in UK Biobank data and 58% of n = 562 matched controls) [28] and worse subjective cognitive complaints in PWH with self-reported poor sleep satisfaction (reported by 62% of n = 435 PWH in China), even after controlling for anxiety and fatigue symptoms [29].…”
Section: Cognitionmentioning
confidence: 99%
“…The Pittsburgh Sleep Quality Index (PSQI) is a well-validated measure of subjective sleep quality [12][13][14] that has been used in a variety of populations [e.g., 12,15,[16][17][18][19] with a global score ≥ 5 distinguishing good from poor sleepers [20]. Although subjective sleep indices such as the PSQI do not necessarily align with polysomnography measures [e.g., 21], they may nevertheless screen relevant aspects of sleep [e.g., 22,23]. Studies in the general population suggest potential relations between poor sleep and impaired cognitive performance [e.g., 24,25].…”
Section: Introductionmentioning
confidence: 99%